Apigenin induced MCF‐7 cell apoptosis‐associated reactive oxygen species. Issue 6 (18th October 2014) - Bai, Haihua; Jin, Hua; Yang, Fen; Zhu, Haiyan; Cai, Jiye
Summary Apigenin is a flavonoid, which has been proved to possess effective anti‐cancer bioactivities against variety of cell lines. However, little is known about its effect on the cell‐surface and the interaction between cell‐surface and the reacting drug. In this study, human breast cancer line (MCF‐7) was selected to be as a cell model to investigate the effects of apigenin on cell growth, proliferation, apoptosis, cellular morphology, etc. MTT assay showed that the growth inhibition induced by apigenin was in a dose‐dependent manner when treated with different concentrations of apigenin while had little cytotoxic effects on human normal cells (MCF‐10A). Fluorescence‐based flow cytometry was used to detect cellular apoptosis and ROS production. The results showed that 80 µM apigenin could effectively induce apoptosis and overproduction of ROS in MCF‐7 cells. Here, atomic force microscopy (AFM) was utilized to detect the shapes and membrane structures of MCF‐7 cells at cellular or subcellular level. The results showed that the control MCF‐7 cells presented typical elongated‐spindle shapes with abundant pseudopodia, while after treated with apigenin, the cells shrunk and became round, the pseudopodia diminished. Moreover, the images of ultrastructure indicated that the cell membrane was composed of nanoparticles of 49 nm, but with the treated concentrations of apigenin increasing, the sizes of membrane particles significantly increased to 400 nm. These results can improve our understanding of apigenin, which can be potentially developed as a new agent for treatment of cancers. SCANNING 36:622–631, 2014. © 2014 Wiley Periodicals, Inc.